Microwave Induced Stereoselective Conversion of Dialkyl 2-(imido-N-yl)-3- (triphenylstibanylidene)succinates to Electron-poor (Z)-N-vinylimides - Ramazani, Ali; Ahmadi, Ebrahim; Noshiranzadeh, Nader (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1 : 1 intermediates, produced in the reaction between triphenylstibine and dialkyl acetylenedicarboxylates, by imides (phthalimide and succinimide) leads to vinyltriphenylstibinium salts, which undergo Michael addition reaction with conjugate base to produce dialkyl 2-(imido - N-yl)-3-(triphenylstibanylidene)succinates. Microwave irradiation was found to catalyze stereoselective conversion of dialkyl 2-(imido-N-yl)-3-(triphenylstibanylidene)succinates to electron-poor (Z)-N-vinylimides in the presence of silica gel in solvent-free conditions at microwave power 0.3 kW in 3 min in high conversions.